2016
DOI: 10.1680/jphmg.15.00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of footing shape on penetration in sand overlying clay

Abstract: This paper reports on a series of centrifuge model tests investigating the effect of shape on the penetration resistance of spudcan and conical footings on sand overlying clay. The effect of footing shape and geometry on single-layer soil has been studied intensely. However, there is still limited understanding for conical footings on sand over clay. In the present study, digital images were captured during penetration of various shapes of half-footing held against a transparent window of a strongbox. The imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…A sand plug is clearly trapped underneath the spudcan, mobilising higher bearing capacity of the soil compared with the single clay case. The measurements from these numerical analyses indicate the height of the sand plug is ~0.9Hs, consistent with the conclusion in Teh (2007) and Hu et al (2016). This manifests that the height of the sand plug was not diminished by interaction with the stiffer underlying clay.…”
Section: Parametric Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…A sand plug is clearly trapped underneath the spudcan, mobilising higher bearing capacity of the soil compared with the single clay case. The measurements from these numerical analyses indicate the height of the sand plug is ~0.9Hs, consistent with the conclusion in Teh (2007) and Hu et al (2016). This manifests that the height of the sand plug was not diminished by interaction with the stiffer underlying clay.…”
Section: Parametric Studiessupporting
confidence: 87%
“…For instance, the punch-through of a spudcan through a layer of sand into underlying clay has been intensively investigated in a geotechnical centrifuge by Craig and Chua (1990), Teh (2007), Lee (2009), Teh et al (2010), Lee et al (2013a), Hossain et al (2016) and Hu et al (2014aHu et al ( , 2016. Table 1 summarises the testing database, with the shear strength of the clay at the sand-clay interface sum ranging from 7.2 to 25.8 kPa and the shear strength gradient in the range of 0 -2.1 kPa/m.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This empirical power law is also adopted here: Equations 6 & 7 provide a slightly higher value of DF for a spudcan. The higher DF value for a spudcan reflects the probable generation of increased lateral stresses during qpeak mobilisation due to the conical underside, as illustrated in Lee et al (2013b), which was also demonstrated by the higher accumulated radial strains underneath the spudcan by Hu et al (2015b).…”
Section: Mathematical Formulation For Peak Resistance Qpeakmentioning
confidence: 93%
“…the friction angle changing with ambient stress level). In addition, image analysis of multi-layered punchthrough centrifuge experiments (see Teh et al 2008;Hossain, 2014;Hu et al 2015b;Ullah et al 2016) indicate that some of the overlying soil becomes entrapped beneath the spudcan foundation during penetration, leading in some instances to increased penetration resistance but a less severe punch-through event. The simple models recommended by SNAME and ISO do not account for these entrapped layers of soil, causing the models to significantly under-predict the penetration resistance during punch-through, and often overpredict the risk associated with uncontrolled leg penetration (Ullah et al 2015).…”
Section: Introductionmentioning
confidence: 99%